(untitled) - Patil, P. B. (Oxford, UK., 2006)
The book present a host of numerical mehtods, their algorithmic presentation and computer program in Visual Basic, FORTRAN and C++. All topic in the book are explicit in nature, self explanatory and student friendly
Keywords: Numerical calculations.,Algorithms.,Computer algorithms.,Trung tâm Học liệu trường ĐHCT,Trung tâm Học liệu trường ĐHCT,Trung tâm Học liệu trường ĐHCT; Số học,Thuật toán,Thuật toán máy tính